Single-Cell RNA Sequencing of the Nucleus Pulposus Reveals Chondrocyte Differentiation and Regulation in Intervertebral Disc Degeneration - Han, Shuo; Zhang, Yiran; Zhang, Xianjuan; Zhang, Hao; Meng, Shengwei; Kong, Meng; Liu, Xiaojie; Ma, Xuexiao (Frontiers in Cell and Developmental Biology, 2022)
The nucleus pulposus (NP), a heterogeneous tissue, is an essential functional component of the intervertebral disc. However, NP cell development route and regulation mechanism in intervertebral disc degeneration (IVDD) remain unknown. Here, we performed single-cell RNA sequencing of six NP samples with normal control, mild degeneration, and severe degeneration. Based on unbiased clustering of gene expression patterns from 30,300 single-cell RNA sequencing, we identified three cell lineage families of macrophages, endothelial, and chondrocyte cells and characterized seven chondrocyte subtypes, and defined two developmental pathways of the chondrocyte cell lineage families in the process of IVDD. Additionally, CellPhoneDB analysis revealed potential interactions between chondrocyte cells and other cells in IVDD. Chondrocytes in one of the differentiated orientations interact with macrophages and endothelial cells and have an inflammatory amplification effect, which were key factors causing IVDD. Collectively, these results revealed the dynamic cell landscape of IVDD development and offered new insights into the influence of NP cells differentiation on extracellular matrix homeostasis during degeneration, providing potential treatment targets for IVDD.